PPROM and Chorioamnionitis following E. Coli UTI - A Case Report - Tullah, Faiqa Awais; Tullah, Sarah Noor; Bhutta, Fatima; Sabir, Sehrish; Kashif, Seemin (Journal of Liaquat University of Medical & Health Sciences, 2025)
A female patient, 38 years old, G2+P0+A1, at 20 weeks plus six days of gestation, was admitted to the emergency with a complaint of watery vaginal discharge for the last 72 hours. There was a hind-water rupture of membranes, and the AmniSure test was positive. She had an OPD visit about a month back, and during that visit, her urine was sent for culture and sensitivity report, which showed E. coli, but she had not taken treatment as she did not come back. Her emergency room baseline labs were in the normal range, and high vaginal swab (HVS) and urine culture and sensitivity results returned negative later. She was asymptomatic for chorioamnionitis. A prophylactic antibiotic was started. Two days later, she developed a fever. She was counseled about septicemia and the risk of maternal death, but she refused. A few hours later, she expelled the fetus and went into hypotension. ERPC (Evacuation of retained products of conception) was done, and one unit of packed red cells was transfused. She was shifted to the ICU. Broad-spectrum IV antibiotics were started. All inflammatory markers were high during her illness. Chest X-ray showed bilateral pleural effusion. She stayed in the ICU for three days and was then discharged. The objective is to discuss a case of septicemia due to preterm premature rupture of membranes (PPROM) and chorioamnionitis, probably following a urinary tract infection (UTI) caused by E. coli, and its management.